Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1212/01.wnl.0000435563.84986.78
|View full text |Cite
|
Sign up to set email alerts
|

Hemosiderin deposition in the brain as footprint of high-altitude cerebral edema

Abstract: MHs detectable by susceptibility-weighted MRI predominantly in the splenium of the CC are long-lasting footprints of HACE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
50
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 10 publications
4
50
0
1
Order By: Relevance
“…The signal dropout without labeling is likely due to blood products, such as hemosiderin, which are caused by the injection and are known to persist for months after injection. 22,24,25 Persistent signal dropout after needle transplantation of labeled and unlabeled cells is consistent with previous reports and remains a confounding factor for negative-contrast MRI cell tracking. Positive-contrast MRI experiments with iron oxide-labeled cells have been developed and are being investigated to address this problem but are not yet in common use.…”
supporting
confidence: 88%
“…The signal dropout without labeling is likely due to blood products, such as hemosiderin, which are caused by the injection and are known to persist for months after injection. 22,24,25 Persistent signal dropout after needle transplantation of labeled and unlabeled cells is consistent with previous reports and remains a confounding factor for negative-contrast MRI cell tracking. Positive-contrast MRI experiments with iron oxide-labeled cells have been developed and are being investigated to address this problem but are not yet in common use.…”
supporting
confidence: 88%
“…Brain MRI performed at low altitude immediately after rescue by helicopter showed oedema in the corpus callosum [19]. Susceptibility-weighted MRI demonstrated a leak of the blood-brain barrier for erythrocytes as evidenced by hemosiderin deposition persisting over years in the corpus callosum and throughout the brain in more severe cases after HACE (figure 1) [20].…”
Section: Ams and Hacementioning
confidence: 99%
“…Though, it is unclear whether these iron deposits are inflicting the normal brain physiology, which needs to be further investigated. Recent human studies have suggested such deposits to be a footprint of HA cerebral edema pathology (Kallenberg et al, 2008;Schommer et al, 2013).…”
Section: Hh-induced Structural Changes In Hippocampusmentioning
confidence: 99%